GPS- & GIS-användning i drivningsprocessen hos Stora Enso SKog AB - Eriksson, Anders (2007)
GPS (Global Positioning system) and GIS (Geographical information system) has been used for planning and inventory in the forest sector for more than ten years. The last years the development has come to equip harvesters and forwarders with GPS and GIS (GIT). The goal with this study was to reach a basis for decision, how Stora Enso Skog should continue its investment in GPS and GIS in harvesters and forwarders. To reach this basis for decision, possible advantages and benefits, disadvantages and problems in the harvesting process was evaluated. The study was made as an interview study with four harvesting managers and ten machine teams. To secure the quality of the results an interview questionnaire was made before the interviews were done. The results showed that GIT will make the harvesting managers work easier. However, the coordination of the GIT-usage at Stora Enso Skog is low witch causes some problems: The education of ICT is insufficient today, which is a hindrance for work and source of irritation. The planning of the harvesting areas are at some of the districts of too low quality, which forces the machine teams to plan the harvesting areas themselves. The harvesting area directives, the landing labels and price lists are sent to the machine teams in many different ways, e-mail is used in a small extent. The advantages of digital information transfer are not efficiently used. GPS and GIS makes navigation easier. Better navigation in combination with that the operators always know the machine position results in more efficient driving and increased productivity. GPS and GIS makes the routines at shift changes more effective. Furthermore the needs of marking cutting area borders will be reduced with GPS and GIS. Based on the results and conclusions from this study, proposals for future development are given to make the implementation of GIT in the harvesting process easier. The suggestions for future development are given in the areas of: coordination of the GIT-usage, improved quality of planning of harvesting areas, the education of ICT, handling of digital information and the harvesting teams computer equipment.